Association of HIV Suppression with Kidney Disease Progression among HIV-Positive African Americans with Biopsy-Proven Classic FSGS - McMahon, Blaithin A. (J Acquir Immune Defic Syndr, 2018)
BACKGROUND: In the era of combined antiretroviral therapy (cART), classic focal segmental glomerulosclerosis (FSGS) is the most common histopathological finding in African American HIV-positive patients with kidney disease. We sought to determine whether HIV suppression is associated with lower risk of progression to end-stage-renal disease (ESRD) among HIV-positive African Americans with biopsy-confirmed classic FSGS. METHODS: HIV-positive African Americans who underwent kidney biopsies at a single tertiary hospital between January 1996 to June 2011 were confirmed as having classic FSGS by the presence of segmental glomerulosclerosis without features of HIV-associated nephropathy (HIVAN). Multivariable Cox proportional hazards models were used to examine the independent association of viral suppression (HIV RNA<400 copies/ml at biopsy) with time to progression to ESRD. RESULTS: Of the 55 HIV-positive African Americans with classic FSGS, 26 had suppressed viral loads at the time of biopsy. Compared to viremic patients, those who were virally suppressed had a significantly higher mean CD4+ cell count (452 vs 260 cell/mm(3), respectively; P=0.02) and median eGFR, (53.5 vs 35.5 mL/min/1.73 m(2), respectively; p=0.002). Adjusting for gender and baseline CD4+ cell count, eGFR and proteinuria, those with HIV RNA levels <400 copis/ml at baseline had a 75% lower risk of progressing to ESRD (HR=0.25; 95% CI: 0.07, 0.88) during a median follow-up time of 2.70 years (IQR: 0.80 – 5.15 years). CONCLUSIONS: HIV suppression is associated with significantly lower risk of progression to ESRD among HIV-infected African Americans with classic FSGS, supporting the potential role of cART for this histopathology in addition to HIVAN among HIV-positive individuals.